The phenomenon of job stress and burnout syndrome in palliative care - Bogusław Stelcer; Bartosz Bilski (Nofer Institute of Occupational Medicine, 2020)
This paper is focused on the analysis of the phenomenon of occupational burnout from the perspectives of the sick person, his/her family and the helper. Practical principles of effective care for dying people and their families were also indicated in order to make the therapeutic team free from the symptoms of occupational burnout. Med Pr. 2020;71(1):69-78